2017
DOI: 10.1002/j.1681-4835.2017.tb00617.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Perception and Quality of ICT‐Based Agricultural Input Information on Use of ICTs by Farmers in Developing Countries: Case of Sikasso in Mali

Abstract: Small-scale cereal farmers dominate agricultural activities in developing countries. These agricultural activities are characterized by low productivity due to lack of agricultural input information. This lack is restrained by the low use of ICTs caused by some factors such as the farmers' perception of ICTs and the ICTs' delivered information quality. We investigated these factors and their effects on ICTs' use by small-scale cereal farmers in developing countries. Sikasso region in Mali was selected as a cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 22 publications
3
22
0
Order By: Relevance
“…In addition, no known study has investigated factors influencing the adoption of mobile phones for marketing by Vietnamese smallholders. Moreover, the findings reported in the existing literature (Alavion et al, 2017;Kante et al, 2017;Mittal & Mehar, 2016;Ogutu et al, 2014;Senthilkumar et al, 2013;Zhang et al, 2016) are not consistent across the studies. For example, Mittal and Mehar (2016) investigated factors that influence the farmers' adoption of ICTs for marketing in India and found that Indian farmers with higher education level and large farm size tended to use ICTs for marketing more than those with a lower education level and small farm size.…”
Section: Introductionmentioning
confidence: 58%
See 2 more Smart Citations
“…In addition, no known study has investigated factors influencing the adoption of mobile phones for marketing by Vietnamese smallholders. Moreover, the findings reported in the existing literature (Alavion et al, 2017;Kante et al, 2017;Mittal & Mehar, 2016;Ogutu et al, 2014;Senthilkumar et al, 2013;Zhang et al, 2016) are not consistent across the studies. For example, Mittal and Mehar (2016) investigated factors that influence the farmers' adoption of ICTs for marketing in India and found that Indian farmers with higher education level and large farm size tended to use ICTs for marketing more than those with a lower education level and small farm size.…”
Section: Introductionmentioning
confidence: 58%
“…The possible reason for this is that CBO members often support each other in terms of human and financial resources, and this can lead to being in a better position to adopt mobile phones for marketing, as well as sharing information between members. In the mainstream literature (Alavion et al, 2017;Kante et al, 2017;Mittal & Mehar, 2016;Ogutu et al, 2014;Senthilkumar et al, 2013), little has been written about the importance and impact of membership of CBOs on smallholders' mobile phone adoption for marketing.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of studies evaluating the use of ICTs in rural areas, even in cases where access is highly subsidized, have found adoption by the rural community to be low (Dossani, Misra, & Jhaveri, ; Gollakota, ; Kuriyan & Toyama, ; Prasad & Ray, ). Many telecenters are underutilized, and the development potential has not been met (Kante, Oboko, & Chepken, ; Sey & Fellows, ). Thus, it is important to understand why so little use is made of ICTs which have so much potential.…”
Section: Introductionmentioning
confidence: 99%
“…[20] in his study observed that the increasing use of mobile phone for in- ICT adoption and use in agriculture will enable the development of strategies to promote their increased use and effectiveness [24]. On the other side, farmer's perception of the role of ICTs in disseminating agricultural information is important in their adoption and use [34]. In a nutshell, ICT can also play a very important role in bridging the information gap in the agricultural sector.…”
Section: Literature Reviewmentioning
confidence: 99%